Characterization of Ikaria Heather Honey by Untargeted Ultrahigh-Performance Liquid Chromatography-High Resolution Mass Spectrometry Metabolomics and Melissopalynological Analysis - Kasiotis, Konstantinos M.; Baira, Eirini; Iosifidou, Styliani; Bergele, Kyriaki; Manea-Karga, Electra; Theologidis, Ioannis; Barmpouni, Theodora; Tsipi, Despina; Machera, Kyriaki (Frontiers in Chemistry, 2022)
Honey represents a valuable food commodity, known since ancient times for its delicate taste and health benefits due to its specific compositional characteristics, mainly the phenolic compound content. “Anama” honey is a monofloral honey produced from the nectar of Erica manipuliflora plant, a heather bush of the Greek island of Ikaria, one of the Mediterranean’s longevity regions. “Anama” is characterized by a unique aroma and taste, with a growing demand for consumption and the potential to be included in the list of products with a protected designation of origin. The aim of this study was to determine the chemical and botanical profile of authentic Anama honey samples and find similarities and differences with honey samples of a different botanical origin from the same geographical area. Untargeted Ultrahigh-Performance Liquid Chromatography-Hybrid Quadrupole-Orbitrap High-Resolution Mass Spectrometry (UHPLC-HRMS) metabolomics study was conducted on authentic heather, pine, and thyme honey samples from Ikaria and neighboring islands. The Principal Component Analysis (PCA), Orthogonal Projections to Latent Structures Discriminant Analysis (OPLS-DA), and differential analysis were performed using the entire metabolic profile of the samples and allowed the identification of chemical markers for sample discrimination. Thirty-two characteristic secondary metabolites (cinnamic acids, phenolic acids, flavonoids, terpenes) and other bioactive phenolic compounds, some of them not previously reported in a heather honey (aucubin, catalpol, domesticoside, leonuriside A, picein among others), emerged as potential chemical indicators of Anama honey. Melissopalynological analysis was also carried out to decipher the botanical and geographical origin of Anama honey. The relative frequency of the pollen of dominant plants of the Ericaceae family and a multitude of nectariferous and nectarless plants contributing to the botanical profile of Anama was evaluated. The identification of the pollen sources enabled a potential correlation of differentially increased secondary metabolites and chemicals with their botanical origin. The physicochemical profile of Anama was also determined, including the parameters of pH, color, electrical conductivity, diastase, moisture, as well as sugars, supporting the high quality of this heather honey.